On The Realization of Grounded RL/RC Parallel Type Simulator - Nutcha Likhitkitwoerakul; Natchanai Roongmuanpha; Worapong Tangsrirat (My University, 2021)
Aπ actively grounded RIJRC parallel type impedance simulator is presented It contains two differential voltage to current converters (DVTCs) as an active element and three passive elements, and can simulate RL or RC parallel-type impedance by the proper selection of the external passive elements. The effect of the DVTC non-idealities on the realized simulator is also analyzed mathematically. The usability of the proposed circuit has been shown on the realizations of active second-order voltage mode highpassand lowpassfilter. PSPICE simulation using TSMC 0.25-jim CMOS technology is performed to demonstrate the behavior of the proposed simulator circuit and its filter applications.
Keywords: Analog and Mixed-Signal Circuit Design; Electrostatic Discharge in Electronics; Advancements in PLL and VCO Technologies